Aerial Target Grouping Method Based on Feature Similarity Clustering - CHAI Hui-min, ZHANG Yong, FANG Min (Jisuanji kexue, 2022)
In order to solve the problems that the number of clusters needs to be given and the sensitivity to the initial positions of the cluster centers while clustering algorithm is utilized for target grouping,a novel aerial target grouping method based on feature similarity clustering is proposed.Firstly,the similarity between targets is calculated and the similarity matrix is constructed.Then,the connected branches of the similarity matrix are calculated to obtained the group center structure and the isolated target points are detected.The number of group center structures is the number of clusters.Finally,the targets which are not belonging to the group center structure and the isolated points are clustered into the closest group center structure.It makes the clustering process no longer depend too much on the initialization of the cluster centers.Experimental results show that the proposed methodcan correctly identify the group center structure and detect the isolated points.Furthermore,its the clustering accuracy is higherthan that of other four clustering algorithms.